Donor relations and sovereignty - Johnny Flentø; Leonardo Santos Simao (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
As a sovereign country, Mozambique initially relied on international solidarity and managed its donor relations well. Donor dependency entailed some loss of agency for the government as it allowed donors to challenge its capacity but never its authority. However, in the last decade, donor countries have expressed disappointment with reforms and challenged the government's legitimacy. This is not only because of developments in Mozambique. Donor countries have become less enthusiastic about long-term, harmonized development cooperation and less concerned with aid effectiveness for poverty alleviation and inclusive growth. Aid budgets are under pressure and development finance is linked more to other donor countries' foreign policy concerns, especially security and commerce. Mozambique should expect increasing instrumentalization of aid budgets by donors. It must be able to address its partners' concerns other than those of poverty alleviation, human rights, and democracy and carefully weigh conflicting interests of its partners against its own long-term interests. The institutions Mozambique developed to deal with donors are not well suited to today's challenges. They focus on less relevant areas of the relationship with foreign countries, which often serve other agendas. Reforms could start with strengthening Mozambique's foreign service as a genuine coordinator of foreign relations and the establishment of greater discipline around national plans and strategies. Institutionalizing strong links between the foreign ministry and key economic ministries under the leadership of the prime minister could help.
Keywords: F35; O1; O2; O43; 330; aid effectiveness; donor dependency; foreign policy; institutions; sovereignty